Bending the Pollution Curve : An Analysis and Prioritization of Pollution Management in Ethiopia - Xie, Jian; Tiruneh, Tamene; Belayhun Woldemeskel, Bereket; Lewis, Christopher Arthur; Schlumpberger, Sven; Croitoru, Lelia; Guttikunda, Sarath (World Bank, Washington DC, 2022)
Pollution and environmental degradation often worsen as countries develop and industrialize. The Environmental Kuznets Curve (EKC) hypothesis suggests that, initially, economic growth increases pollution up to a certain income threshold, and then it begins to decrease pollution. Pollution reduction is not inevitable, however. As one of the fastest-growing economies in Africa, Ethiopia has been facing natural resource depletion and pollution problems which threaten to slow or impede development gains. The country must actively improve its pollution management practices and mitigate the impact of pollution on its economy, public health, and the natural environment as much as possible. This report aims to identify, diagnose, and evaluate air, water, and solid waste pollution issues facing Ethiopia and advise governments on developing and prioritizing pollution management interventions through a long-term perspective. It assesses the impacts of pollution problems and estimates the economic costs of pollution in selected study cities, which provide an economic basis for prioritizing and recommending pollution management interventions and programs. The report concludes that, with a good understanding and public awareness of pollution problems, strong political will, and sound strategies for pollution management, Ethiopia may bend the EKC and avoid the “pollute first, clean up later” development path that industrialized countries have taken—creating the chance for a cleaner environment, a healthier population, and a stronger and sustainable development progress.